Preparation of Simple Accounting Bookkeeping Based on SAK EMKM for Banana Chips MSMEs: Penyusunan Pembukuan Akuntansi Sederhana Pada UMKM keripik pisang Desa Citaringgul, Bogor - Musa Mulyadi; Sri Harini; Andi Hardiansyah; Saepul Anwar; Dini Aulia; M Arifin; Sari Ramadhani (Institut Riset dan Publikasi Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy. However, most MSMEs face financial management problems, especially in recording and reporting transactions. This study aims to design a simple accounting bookkeeping model for banana chips MSMEs and evaluate its conformity with basic accounting principles and the EMKM Financial Accounting Standards (SAK EMKM). The research method used was a qualitative descriptive approach through direct interviews with business owners, followed by documentation and preparation of financial records. The results show that the banana chips MSME had not implemented routine bookkeeping, causing difficulties in separating personal and business finances, calculating production costs, and identifying net profit. Through mentoring, a simple bookkeeping system was developed that includes the calculation of the cost of goods sold (COGS), as well as daily records of income, expenses, and cash balances. The findings indicate that this simple bookkeeping system has met the basic principles of accounting by providing relevant and reliable financial information, although it has not fully complied with SAK EMKM, which requires the presentation of a balance sheet, income statement, and notes to the financial statements. In conclusion, the simple bookkeeping model is effective as a preliminary step for MSMEs in transitioning toward standardized financial reporting in accordance with SAK EMKM